The Role of the Political Development Council in the Enhancement of National Reconciliation - thanasthit, uraiwan (King Prajadhipok’s Institute Journal, 2020)
During the past four years (2008–2012) the principal role of the Political Development Council has been to strengthen democracy at the grassroots level. Most of Thai society consists of grassroots people. The Council aims to implement democracy as a structural base. It emphasizes democracy in the community through decentralization. When people experience real democracy and are free, they are able to reveal their intelligence and strength. Conflict and unequal treatment will be reduced, leading to reconciliation and security in the nation. Because the main contribution of the Council is focused on grassroots democracy, the outcome is not evident over a short time. Even though the target has not yet been fully attained, it is nevertheless a great endeavor to bridge the gap. The Council tries not to let violence occur among Thais. The Council tries instead to integrate between representative democracy and participatory democracy. The highest goal of reconciliation is to enable all people to receive fair and equal treatment, and to let them feel that they receive honor and acceptance from the state. The government has to understand more about the customs, culture, religion, and economy of all groups of people. In the end everything will move in a positive direction and happiness will return to our country.